PTH-152 Nurse Delivered day Case Paracentesis - a Single Centre Experience. (4th June 2013) - Tobin, L; Patani, O D; Hood, S; Sturgess, R; Stern, N
Abstract : Introduction: Refractory ascites is a debilitating consequence of end stage liver and other diseases. Treatment options are limited and include recurrent large volume paracentesis (LVP). Admission for LVP requires usage of in-patient beds which are in high demand and have a high cost. Since 2009 we have introduced day case paracentesis and trained a Hepatology clinical nurse specialist (CNS) to perform LVP for stable patients as day cases. Methods: We aimed to evaluate our service development to assess the safety and success rate of day case LVP and particularly a nurse delivered day case LVP service. Initially, day case LVP was coordinated by the CNS with trainees in gastroenterology performing the procedure; subsequently we trained up and assessed the CNS in performing LVP independently. A retrospective audit, evaluating all day case LVP performed since the introduction of the service was performed. Aetiology of ascites and severity of liver disease (Child Pugh), volume drained and complications related to drainage were all recorded. The proportion of cases performed by doctors and the CNS were noted to determine relative outcomes. All cases of LVP for ascites due to cirrhosis were given 20% human albumin solution as per local protocol. Results: 108 LVP performed (in 42 patients). 62 (57.4%) performed by the CNS. The cause of ascites was cirrhosis in 36 patients (94 LVP) and malignancy in 6 patients (14 LVP). In cirrhotic patients, median Child Pugh score was 8 (range 7–11). 107 (99.1%) of attempts at LVP were successful with 106 (98.1%) drains sited with a single needle pass. The volume of ascites drained typically was 12–16 litres (range 3–26). Complications included local skin infection requiring oral antibiotics in 1 case (0.9%) and leakage of ascites requiring suturing in 11 (10.2%) procedures. Most cases of local leakage were in those with malignant ascites (63.6%). There were no long term or serious complications and no unplanned admissions following on from day case LVP. There was no difference in success or complication rate between those LVP performed by the CNS or medical staff. Conclusion: Nurse delivered day case LVP is a safe and effective method of managing patients with refractory ascites. It is a method of relieving the burden on the hospital bed base in a sustainable and safe way. In addition, we would anticipate significant cost savings for this model compared to admission for LVP. Disclosure of Interest: None Declared.